Predictors of Recurrent Venous Thrombosis After Cerebral Venous Thrombosis: Analysis of the ACTION-CVT Study. (22nd November 2022) - Shu, Liqi; Bakradze, Ekaterina; Omran, Setareh Salehi; Giles, James; Amar, Jordan; Henninger, Nils; Elnazeir, Marwa; Liberman, Ava; Moncrieffe, Khadean; Rotblat, Jenny; Sharma, Richa; Cheng, Yee; et al.
Abstract : Background and Objective: Cerebral venous thrombosis (CVT) is a rare cause of stroke carrying a nearly 4% risk of recurrence after 1 year. There are limited data on predictors of recurrent venous thrombosis in patients with CVT. In this study, we aim to identify those predictors. Methods: This is a secondary analysis of the ACTION-CVT study which is a multicenter international study of consecutive patients hospitalized with a diagnosis of CVT over a 6-year period. Patients with cancer-associated CVT, CVT during pregnancy, or CVT in the setting of known antiphospholipid antibody syndrome were excluded per the ACTION-CVT protocol. The study outcome was recurrent venous thrombosis defined as recurrent venous thromboembolism (VTE) or de novo CVT. We compared characteristics between patients with vs without recurrent venous thrombosis during follow-up and performed adjusted Cox regression analyses to determine important predictors of recurrent venous thrombosis. Results: Nine hundred forty-seven patients were included with a mean age of 45.2 years, 63.9% were women, and 83.6% had at least 3 months of follow-up. During a median follow-up of 308 (interquartile range 120–700) days, there were 5.05 recurrent venous thromboses (37 VTE and 24 de novo CVT) per 100 patient-years. Predictors of recurrent venous thrombosis were Black race (adjusted hazard ratio [aHR] 2.13, 95% CI 1.14–3.98, p = 0.018), history of VTE (aHR 3.40, 95% CI 1.80–6.42, p < 0.001), and the presence of one or more positive antiphospholipid antibodies (aHR 3.85, 95% CI 1.97–7.50, p < 0.001). Sensitivity analyses including events only occurring on oral anticoagulation yielded similar findings. Discussion: Black race, history of VTE, and the presence of one or more antiphospholipid antibodies are associated with recurrent venous thrombosis among patients with CVT. Future studies are needed to validate our findings to better understand mechanisms and treatment strategies in patients with CVT.